Optical and Thermoelectric Behavior of Phagraphene with Site‐Specific B‐N Co‐Doping. Issue 9 (10th July 2022) - Ghosh, Mainak; Ghosal, Supriya; Jana, Debnarayan
Abstract: Phagraphene is a theoretically predicted s p 2 $sp^2$ hybridized, se‐mimetallic allotrope of graphene. The semimetallic nature of phagraphene is robust against external strain and B‐N co‐doping. Being experimentally realized in a nanoribbon form, this is quite fascinating in the present scenario. In this theoretical study, optical and thermoelectric properties of phagraphene and its site‐dependent B‐N co‐doped analogous configurations are critically investigated employing density functional theory. As a consequence of inherent rectangular symmetry and direction‐dependent behavior of the structures, anisotropic optical responses are obtained. The strain‐induced optical responses further confirm these observations. Different positions of the optical peaks for distinct configurations lead to an elegant way of structural identifications. The absorption spectra of the structures reveal that low‐energy optical transitions take place due to p z $p_z$ orbitals. Besides, static dielectric constant and refractive index are enhanced for the co‐doped structures. Furthermore, the thermoelectric responses of the structures are explored by adapting the semi‐classical Boltzmann transport equation. Importantly, a significantly higher figure of merit has been perceived, which is quite uncommon among graphene allotropes. Abstract : Depending upon the crucial electronic behavior of phagraphene and its B‐N co‐doped analogues, anisotropic optical behaviors and thermoelectric characteristics are critically explored. Optical absorption confirms the presence of low‐energy peaks due to the pz orbitals. Besides, semi‐classical Boltzmann's theory predicts that phagraphene possesses a significantly higher figure of merit among all other graphene allotropes.